TTTCA Repeat Expansion of SAMD12 in a New Benign Adult Familial Myoclonic Epilepsy Pedigree - Liu, Chaorong; Song, Yanmin; Yuan, Ying; Peng, Ying; Pang, Nan; Duan, Ranhui; Huang, Wen; Qin, Xuehui; Xiao, Wenbiao; Long, Hongyu; Huang, Sha; Zhou, Pinting; et al. (Frontiers in Neurology, 2020)
Benign adult familial myoclonic epilepsy (BAFME) is an autosomal dominant disorder characterized by adult-onset cortical myoclonus with or without seizures. Recently, it was reported to be associated with an intronic TTTTA/TTTCA expansions. To investigate whether these abnormal expansions are involved in our new pedigree from China, whole exome sequencing (WES) and repeat-primed polymerase chain reaction (RP-PCR) analysis were performed to detect potential mutation in pedigree members. Neither causal mutations co-segregated with the disease in the family nor any novel mutation was identified through WES. While an abnormal TTTCA expansion in SAMD12 was identified by RP-PCR and then proved to be co-segregated in the pedigree. All the 12 alive affected individuals (M/F = 4/8; average age = 46.7 years old, range from 27 to 66) showed typical characteristics of BAFME. In addition, maternal clinical anticipation was observed in six mother/child pairs. In conclusion, our study offered the evidence of intronic pentanucleotide expansions in SAMD12 from a new Chinese BAFME pedigree, which further confirmed the association between this expansion and the pathogenesis of BAFME.